(3YbO GdLeGf aj WHGFY efGaY GdMjhGf hGdEfSGfs - (3YHjO Gddg Hf LHQFjd Hf YHjO Gddg Hf HNJjThY, CHh SYjO,J (B453 (3g` s
(3ChdgG (B:s
(3GdMeO ddg GdPi aVd BOe hPQjJg Ydi cKjQ eef Ndb JaVjdkG s
(3BNQgG (B:s
(3adfNJe GdcJGH hfQLh ef Gddg Ld LdGdg Cf Jchf bO HdZfG GdZQV hGfJgjfG Edi GdeQGO HYhf Gddg hbhJg hMSf Jhajbg s
(3PcQ ajg eG JaQb ef cJH GdYdeGA hUMa GdbOeGA ef efGaY GdMjhGf hNhGUgG heG GNJHQ HGdJLGQH heG NU Gddg Hg GdEfSGf ef GdWHGFY GdYLjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B192 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B6 - (3U (B238s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B3 - (3bSe (B4 - (3U (B75 s
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdeUQjI (B((3WHjYjGJ (B297) s
Keywords: (3GdcjejGA h GdWHjYjGJs